2021
DOI: 10.3389/fpsyg.2021.576089
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Body Image Self-Discrepancy With Female Gender, Calorie-Restricted Diet, and Psychological Symptoms Among Healthy Junior High School Students in Japan

Abstract: Background: Body image self-discrepancy reflects a preference for weight loss regardless of normal body size and is a distorted cognition that may be a precursor to eating disorders. The aim of this study was to investigate factors associated with body image self-discrepancy among healthy junior high school students in Japan.Method: This cross-sectional study was conducted at one junior high school in Saitama, Japan, in December 2016. After excluding obese participants (defined as 20% above their ideal weight)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 36 publications
2
10
1
Order By: Relevance
“…Height and weight were self-reported to calculate an average BMI of 23.6 kg/m 2 , which is similar to a UConn sample of young adult college women recruited prior to the pandemic [ 46 ]. Most of the women did not have a large discrepancy in their body size perception, contrary to the expected higher body size discrepancies reported in the literature [ 73 , 74 ]. The sample displayed a moderate level of dietary restraint, which is similar to a pre-pandemic sample but with a different dietary restraint measure [ 46 ].…”
Section: Discussioncontrasting
confidence: 89%
See 2 more Smart Citations
“…Height and weight were self-reported to calculate an average BMI of 23.6 kg/m 2 , which is similar to a UConn sample of young adult college women recruited prior to the pandemic [ 46 ]. Most of the women did not have a large discrepancy in their body size perception, contrary to the expected higher body size discrepancies reported in the literature [ 73 , 74 ]. The sample displayed a moderate level of dietary restraint, which is similar to a pre-pandemic sample but with a different dietary restraint measure [ 46 ].…”
Section: Discussioncontrasting
confidence: 89%
“…The Scale consists of 9 figures (males and females) representing underweight to obese body types [ 84 , 89 ], including figures 1–2 as underweight, 3–4 as normal weight, 5–6 as overweight, and 7–9 as obese. The body size discrepancy variable used in the analysis was ideal body figure subtracted from current figure as a proxy of body dissatisfaction [ 73 , 74 , 90 , 91 ]. The variable was treated continuously to test relationships with responses to information, motivation, confidence and categorical as Body Discrepancy (scores greater or less than 1) versus No Body Discrepancy (scores 0 or ±1) to describe the sample and test survey and message feasibility.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although MTF is widely prescribed worldwide as a first-choice medication for T2DM [ 47 ], few studies have seen the light regarding use by gender. Although women are more concerned than men about their body image [ 48 ], and MTF may show a modest effect on weight loss [ 49 ], women are usually prescribed lower MTF doses compared to men (and they report more gastrointestinal side effects) [ 50 ]. In a Dutch study, although women reported/experienced more gastrointestinal drug reactions during the first months of MTF treatment, the rate of the latter dropped in a way analogous to that in men [ 50 ].…”
Section: Sex/gender Differences Using Mtfmentioning
confidence: 99%
“…Despite their normal weight, high school students tend to observe episodic diets, which can contribute to the development of eating disorders [18,19].…”
Section: Fig 3 Topics Of Healthy Eating That Interest High School Stu...mentioning
confidence: 99%